Effect of Implementation ERP on Profitability of Firm Value Sector Manufacture Companies Listed on the Indonesia Stock Exchange - Berliana Lintang Delvira; Dedi Kurniawan (Journal of Applied Accounting and Taxation, 2022)
The research aims to analyze the effect of Enterprise Resources Planning system implementation on the profitability of firm value. This research sample uses purposive sampling with criteria manufacturing corporations have listed in BEI for three years, 2017-2019. This research uses a quantitative method such as analyzing descriptive and hypothesis tests with partial, simultaneously, chi-square, and paired sample t-tests. This research proves that not every variable can be affected by ERP. Partially ratio ROE is a significant variable before and after ERP implementation. Paired sample t-tests have significant variables ROA, ROE, and ROI have significant differences between before and after implementation ERP showed by profitability.